"Jack‐of‐all‐trades" is parthenogenetic. Issue 6 (23rd June 2022) - Maraun, Mark; Bischof, Paul S. P.; Klemp, Finn L.; Pollack, Jule; Raab, Linnea; Schmerbach, Jan; Schaefer, Ina; Scheu, Stefan; Caruso, Tancredi
Abstract: Sex is evolutionarily more costly than parthenogenesis, evolutionary ecologists therefore wonder why sex is much more frequent than parthenogenesis in the majority of animal lineages. Intriguingly, parthenogenetic individuals and species are as common as or even more common than sexuals in some major and putative ancient animal lineages such as oribatid mites and rotifers. Here, we analyzed oribatid mites (Acari: Oribatida) as a model group because these mites are ancient (early Paleozoic), widely distributed around the globe, and include a high number of parthenogenetic species, which often co‐exist with sexual oribatid mite species. There is evidence that the reproductive mode is phylogenetically conserved in oribatid mites, which makes them an ideal model to test hypotheses on the relationship between reproductive mode and species' ecological strategies. We used oribatid mites to test the frozen niche variation hypothesis; we hypothesized that parthenogenetic oribatid mites occupy narrow specialized ecological niches. We used the geographic range of species as a proxy for specialization as specialized species typically do have narrower geographic ranges than generalistic species. After correcting for phylogenetic signal in reproductive mode and demonstrating that geographic range size has no phylogenetic signal, we found that parthenogenetic lineages have a higher probability to have broader geographic ranges than sexual species arguing against the frozen niche variation hypothesis. Rather, the results suggest that parthenogenetic oribatid mite species are more generalistic than sexual species supporting the general‐purpose genotype hypothesis. The reason why parthenogenetic oribatid mite species are generalists with wide geographic range sizes might be that they are of ancient origin reflecting that they adapted to varying environmental conditions during evolutionary history. Overall, our findings indicate that parthenogenetic oribatid mite species possess a widely adapted general‐purpose genotype and therefore might be viewed as "Jack‐of‐all‐trades." Abstract : Our results suggest that parthenogenetic oribatid mite species are more generalistic than sexual species supporting the general purpose genotype hypothesis. Our findings indicate that parthenogenetic oribatid mite species possess a widely adapted general‐purpose genotype and therefore might be viewed as "Jack‐of‐all‐trades".